Legitimacy through representation? Media sources and discourses of offshore wind development - Diamond, Emily P.; Damato, Nikol; Smythe, Tiffany; Bidwell, David (Frontiers in Communication, 2024)
Introduction The choice of which individuals and entities to include as sources in newspaper articles is an important decision for journalists, in large part because they can shape how readers understand the issue and which arguments become most salient. This is particularly important for issues that are relatively new or unknown to readers. The growing topic of offshore wind in the United States is a prime example of an issue that many people are encountering for the first time via media reporting. This issue has also proven to be highly divisive, with heated oppositional arguments being promoted by different entities. This study seeks to understand which entities are being represented in media coverage of offshore wind, and the different framing strategies that various entities use in quotes about the first two large-scale projects in the United States, South Fork Wind and Vineyard Wind I. Methods We use a newspaper content analysis to identify and code the sources quoted in articles reporting on South Fork Wind and Vineyard Wind I from 2013-2022, as well as the emphasis frames used by each entity. Results We find that coverage varies in the two cases, but developers and political officials are quoted most frequently. As these entities tend to use frames highlighting the benefits of offshore wind more frequently than the risks, those perspectives dominate news coverage. Meanwhile, perspectives of community members and impacted industries such as the fishing industry are represented less frequently in news coverage. Discussion These findings help explain the dominance of certain frames and perspectives in offshore wind, and they raise important questions about which voices are legitimized through representation in news media.